1989
DOI: 10.1021/jm00130a005
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid agonists. Enzymic resolution, x-ray structure, and enantioselective activities of (R)- and (S)-bromohomoibotenic acid

Abstract: The enantiomers of alpha-amino-4-bromo-3-hydroxy-5-isoxazolepropionic acid (4-bromohomoibotenic acid, Br-HIBO, 1) a selective and potent agonist at one class of the central (S)-glutamic acid receptors, were prepared with an enantiomeric excess higher than 98.8% via stereoselective enzymic hydrolysis of (RS)-alpha-(acetylamino)-4-bromo-3-methoxy-5-isoxazolepropionic acid (4) using immobilized aminoacylase. The absolute configuration of the enantiomers of Br-HIBO was established by X-ray crystallographic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 2 publications
0
36
1
1
Order By: Relevance
“…Crystal data (3) 112.8(2) 1.425 (3) 112.6(2) 1.420 (3) 112.9(2) References: AMIOXO, Brehm (1977); HAPIOX, Brehm & KrogsgaardLarsen (1974); HMUSCM, ISAZOL, Brehm & Larsen (1976); DECJAW/DECJAW01, Krogsgaard-Larsen et al (1985); DEVFEP, Brehm et al (1985); GASKUG, Madsen et al (1988); RSAMPA, Honor6 & Lauridsen (1980); SEBFUA, Hansen et al (1989); OPOXAZ/OPOXAZ01, Biagini et al (1969a,b); (R)-APPA, Ebert et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…Crystal data (3) 112.8(2) 1.425 (3) 112.6(2) 1.420 (3) 112.9(2) References: AMIOXO, Brehm (1977); HAPIOX, Brehm & KrogsgaardLarsen (1974); HMUSCM, ISAZOL, Brehm & Larsen (1976); DECJAW/DECJAW01, Krogsgaard-Larsen et al (1985); DEVFEP, Brehm et al (1985); GASKUG, Madsen et al (1988); RSAMPA, Honor6 & Lauridsen (1980); SEBFUA, Hansen et al (1989); OPOXAZ/OPOXAZ01, Biagini et al (1969a,b); (R)-APPA, Ebert et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…34 These structures strongly suggest that the hydrogen bond architecture through water molecules and involving the isoxazole hydroxy group of (S)-Br-HIBO and Tyr702 of the GluR2 ligand binding domain is crucial for the observed subtypeselectivity of (S)-Br-HIBO, 34 as previously suggested by Banke et al 70 The very low AMPA receptor affinities observed for (R)-HIBO and (R)-Br-HIBO (Table 3) most likely reflect the enantiomeric purity obtained, rendering the HIBO analogs highly stereoselective at AMPA receptors. However, both the S-and R-enantiomers of the HIBO analogs generally show affinity in CaCl 2 -dependent [ 3 H]Glu binding and potent activity after quisqualic acid priming in electrophysiological experiments, 67,68,71 suggesting interaction with transport mechanisms different from the synaptic reuptake systems. Even though (R)-Bu-HIBO was shown to be inactive per se at AMPA receptors, coadministration of (S)-Bu-HIBO with a fixed concentration of (R)-Bu-HIBO markedly potentiated the concentration-response curve obtained in the cortical wedge preparation (Fig.…”
Section: Isoxazole-based Glu Homologsmentioning
confidence: 99%
“…10,11 The synthesis of cyclic amino acids became a key issue within rational drug design and structure -activity relationship (SAR) studies (Fig. 1).…”
mentioning
confidence: 99%